Response to AM fungi and Azospirillum in growth of Vigna radiata L. Hub - P. Thamizhiniyan*, M. Panneerselvam and (Recent Research in Science and Technology, 2011)
Effect of AM fungi and Azospirillum application was studied on growth parameters in Green gram (Vigna radiata L.). The pot culture experiment was conducted by using AM fungi and Azospirillum. The result showed increased growth parameters (shoot, root length, number of leaves, fresh and dry weight). The AM fungi inoculated plants showed higher, when compared to the Azospirillum treated plants.